The ties that bind and bond: socio-cultural dynamics and meanings of remittances among Congolese migrants in Johannesburg - Kankonde, Bukasa Peter (My University, 2010)
ABSTRACT The thesis investigates how transnational familial ties and socio-cultural dynamics shape migrants‘ remitting behavior and inform their relationships. It shows that most research on remittances fails to capture the personal and social significance remittances have for migrants, embedded not only in their transnational social relations, but also in cultural contexts. Drawing on empirical qualitative and quantitative research amongst Congolese migrants in Johannesburg, the study argues that migrants remit mainly in a bid to escape social death by fostering familial belonging and sustaining social status. It shows that socio-cultural influences and internalized social stereotypes about the economic effects of emigration shape migrants‘ awareness of the role expectations their communities of origin hold in relation to them. This internalization of role expectations subjects migrants to such a social pressure that they often feel a compelling need to be perceived as financially ―successful‖ as well as ―valid‖ and ―good‖ family members – not only in their communities of origin but also among other migrants. In this context, remittances become a fundamental measure and criterion that shapes migrants‘ sense of belonging and social and familial inclusion or exclusion. For individual migrants, remittances play an essential instrumental role portraying positive images for themselves and, at the same time, are seen as a means to avoid social stigmatization and exclusion.
Keywords: transnational families; remittances; identity; belonging; social death; socio-cultural dynamics and meanings